Service Branding and Performance of Insurance Firms in Ekiti State, Nigeria - Olatunde Ogunode, Philips; Niyi Abereola, Samuel; Sunday Olowe, Temitope (British Journal of Marketing Studies, 2023)
The apparent poor performance in the insurance sector occasioned by poor service branding is the major factor that triggers this study. The study examined the influence of brand meaning, brand awareness, brand image and external brand communication on performance of Insurance firms in Ekiti State. Survey research design was adopted in executing the study with a population of 257 Insurance employees in Ekiti State. Since the population was relatively small, the entire population was used as a census. Primary data were collected using self-administered questionnaire distributed to employees of insurance companies in Ekiti State. The data generated from the questionnaire were subjected to statistical analysis and the hypotheses were tested using Correlation Coefficient with the aid of Statistical Package for Social Sciences (SPSS) version 25.0. The findings revealed that all the independent variables (brand meaning, brand awareness, brand image and external brand communication) have significant influence on performance of insurance firms in Ekiti State. Hence, the study concluded that a statistically significant and positive association exists between service branding and performance of Insurance firms in Ekiti State. Hence the study recommended that management of insurance companies should put strong policies on service branding in place so as to improve profitability and market share of insurance firms operating in Ekiti State.